Удосконалення технології морозива з овочевою сировиною - Сапіга, Вікторія Ярославівна (My University, 2023)
Дисертаційну роботу присвячено удосконаленню технології морозива з овочевою сировиною за рахунок попередньої активації її функціонально-технологічних властивостей, розроблення рецептурного складу морозива нових видів з натуральними інгредієнтами та уточнення технологічних режимів його виробництва. Науково обґрунтовано вибір поліфункціональної овочевої сировини для формування комплексу характерних для морозива молочного з овочевою сировиною, морозива овочевого і щербету органолептичних, фізико-хімічних та мікробіологічних показників якості. Доведено технологічну доцільність попередньої активації пюре з моркви столової, буряка столового, броколі, кабачків і томатів шляхом часткової деструкції протопектину різними способами перед внесенням їх у суміші морозива. Виявлено більшу ефективність ферментативного гідролізу протопектину в овочевих пюре, порівняно з кислотним гідролізом, що дозволяє підвищити вихід розчинного пектину на 8…12 % за менших енергетичних витрат у 1,15…1,25 %. Оптимізовано параметри процесу ферментолізу протопектину за ступенем його гідролізу (не нижче 90%) для овочевої сировини різних видів з вмістом пектинових речовин 0,22…2,56 %. Для забезпечення високої ефективності ферментативного гідролізу протопектину моркви та буряку потреба у ферменті є найбільшою і становить від 0,1 до 0,2% за раціональної тривалості процесу ферментації (від 120-180 хв до 240 хв). Для кабачків, броколі і томатів доза ферменту зменшується до 0,05-0,10% за скорочення тривалості ферментолізу (60-120 хв). Подовження тривалості процесу ферментолізу внаслідок надмірного гідролізу пектинових речовин призводить до зниження ефективної в’язкості і тиксотропної здатності овочевих пюре. Встановлено що ферментація і термокислотне оброблення знижують активність води у 1,06…1,12 % в овочевих пюре за рахунок підвищеного вмісту в них розчинного пектину. Серед досліджуваних овочевих пюре найефективнішими з технологічної точки зору є пюре з моркви, буряку і кабачків за вищого вмісту в них розчинного пектину, а пюре з броколі та, особливо, пюре з томатів доцільно використовувати у комбінації з іншими овочевими пюре. Часткова втрата функціонально-технологічних властивостей овочевої сировини за надмірного гідролізу пектинових речовин негативно відбивається і на реологічних характеристиках сумішей морозива. Ферментована овочева сировина внаслідок більшого вмісту розчинного пектину та утворення структуруючих комплексів між полісахаридами та молочними білками суттєвіше впливає на реологічні характеристики молочних сумішей. Ефективна в’язкість практично незруйнованої структури сумішей молочних з овочевими пюре, гідролізованими кислотним способом, дещо нижча за суміші з пюре ферментованими, що пояснюється розріджуючою дією пектинази на фрагменти оболонок рослинних клітин. Ефективна в’язкість відновленої структури сумішей молочних з ферментованими овочевими пюре виявляють високу тиксотропну здатність за рахунок не лише високого вмісту розчинного пектину, але й розм’якшених рослинних волокон. Такі суміші можна віднести до систем з вираженою коагуляційною структурою і характерними тиксотропними властивостями. Для альтернативної заміни стабілізуючих систем у складі морозива з низьким вмістом жиру та сухих речовин обрано розчинне харчове волокно − β-глюкан вівсяний. Встановлено, що порівняно з молочно-білковими концентратами, β-глюкан виявляє вищу технологічну активність у складі сумішей морозива у тому числі за сполучення з розчинним пектином овочевого пюре. Доведено, що ефективна в’язкість сумішей морозива з β-глюканом вівсяним у кількості 0,5-1,0% знаходиться в діапазоні рекомендованих значень. Суміші морозива молочного з β-глюканом вівсяним характеризуються високою тиксотропною здатністю, що повністю забезпечує реалізацію технологічного циклу виробництва морозива на етапі дозування та формування його порцій. Комплексне застосування β-глюкану і ферментованих овочевих пюре за високого вмісту розчинного пектину та наявності розм’якшених рослинних волокон, дозволяє суттєво покращити в'язкісно-швидкісні характеристики сумішей: ефективна в'язкість підвищується на 11,5…15,9%, а ступінь відновлення у середньому на 10%. Морозиво молочне низькожирне з овочевою сировиною та β-глюканом, як натуральним стабілізатором структури, набуває характерної кремоподібної консистенції. Підвищення збитості та опору таненню морозива з β-глюканом обумовлено утворенням специфічної вторинної пінної мікроструктури, яка відрізняється наявністю додаткового каркасу з мікробульбашок, який обгортає більш крупні повітряні включення включення і надає їм додаткової механічної стійкості під час отеплення. Ферментовані пюре за вмісту не менше ніж 1,0 % розчинного пектину, чинять найбільший вплив на структурно-механічні характеристики сумішей низькожирного молочного морозива у всіх його комбінаціях з іншими структуруючими інгредієнтами. Суміші молочного морозива з вівсяним β-глюканом і овочевими пюре на нижчих частотах вимірювання в’язко-пружних властивостей виявляють пружність, але після перевищення певного значення частоти структура руйнується і суміші виявляють більшу в’язкість, ніж еластичність, що дозволить більш інтенсивно насичувати суміші повітрям під час фризерування. Виявлено кореляцію між в’язкістю, активністю води і поверхневим натягом сумішей низькожирного морозива, що пояснюється міжмолекулярною взаємодією між макромолекулами гідроколоїдів та активним зв’язуванням вільної води комплексом низькомолекулярних і високомолекулярних сполук. Альтернативною заміною стабілізаційної системи Cremodan SI 320 у кількості 0,5% у складі молочного морозива з низьким вмістом жиру є комплекс натуральних інгредієнтів – β-глюкану вівсяного і ферментованих пюре у кількостях 0,5 і 15-25%, відповідно. Досліджено функціонально-технологічні властивості пектиновмісних пюре з овочів у складі морозива за їх варійованого вмісту в діапазоні від 10 до 35%. За критерії якості досліджуваних зразків обрано органолептичні показники, масову частку розчинного пектину, активність води та активну кислотність сумішей молочних з овочевою сировиною, збитість і опір таненню морозива молочного з овочевою сировиною. Встановлено, що гідроліз протопектину знижує активність води в овочевих пюре і сумішах молочних з овочевою сировиною, відповідно до загального вмісту розчинного пектину. Доведено, що у заданому діапазоні вмісту сухі речовини овочевих пюре підвищують опір морозива до танення. За комплексом показників якості зразків морозива молочного з овочевою сировиною визначено, що найбільшою технологічною активністю володіють овочеві пюре з моркви, буряку та кабачків, а дещо нижчою – пюре з броколі і найнижчою пюре з томатів. На основі порівняльного аналізу результатів дослідження розроблено рекомендації щодо складання базових (типових) рецептур морозива молочного з овочевою сировиною, щербету та морозива овочевого з врахуванням раціональних діапазонів вмісту ферментованих овочевих пюре, у тому числі за сполучення різних видів овочевих пюре. Уточнено технологічні режими визрівання сумішей морозива з овочевою сировиною різного хімічного складу. Досліджено нормативні показники якості морозива молочного з овочевою сировиною, овочевого і щербету, у тому числі впродовж зберігання. Соціальний ефект від впровадження удосконаленої технології морозива із застосуванням овочевої сировини полягає в розширенні асортиментної лінійки морозива підвищеної харчової цінності на основі виключно натуральної сировини, заощадженні сировини тваринного походження, скороченні тривалості технологічного циклу класичної схеми виробництва морозива. Достовірність отриманих результатів підтверджено використанням сучасних методик досліджень, відповідного обладнання, використанням математичних засобів для опрацювання результатів. Наукові положення та рекомендації підтверджені лабораторними дослідженнями проведеними в лабораторія університетів України та Польщі. Наукову новизну розробки підтверджено позитивним рішенням Державного департаменту інтелектуальної власності про видачу патентів України. The dissertation is devoted to the improvement of the technology of ice cream with vegetables due to the preliminary activation of the functional and technological properties of vegetable raw materials, the development of the formulation of new types of ice cream with natural ingredients, and the clarification of the technological modes of its production. The choice of polyfunctional vegetable raw materials for the formation of a complex of sensory, physicochemical and microbiological quality indicators of milk-vegetable, vegetable and sherbet ice cream, was scientifically explained. The technological expediency of preliminary activation of puree from table carrots, table beets, broccoli, zucchini and tomatoes by partial destruction of protopectin in various ways before adding them to the mix for the production of ice cream has been proven. The higher efficiency of enzymatic hydrolysis of protopectin in vegetable purees was revealed, compared to acid hydrolysis, which allows increasing the yield of soluble pectin by 8-12% with lower energy costs in 1,15…1,25 %. The parameters of the process of protopectin enzymolysis were optimized according to the degree of its hydrolysis (not lower than 90%) for various types of vegetable raw materials with the content of pectin substances from 0.22 to 2.56%. To ensure high efficiency of enzymatic hydrolysis of carrot and beet protopectin, the need for enzyme is the highest (from 0.1 to 0.2%) for a rational duration of the fermentation process (from 120-180 min to 240 min). For zucchini, broccoli, and tomatoes, the dose of the enzyme is reduced to 0.05-0.10% for reducing the duration of enzymeolysis (60-120 minutes). Prolongation of the process of enzymolysis due to excessive hydrolysis of pectin substances leads to a decrease in the effective viscosity and thixotropic ability of vegetable purees. It has been showed that fermentation and thermal acid treatment of puree reduce the water activity in 1,06…1,12 % in vegetables due to the increased content of soluble pectin. Among the studied vegetable purees, the most effective from a technological point of view are carrot, beet and zucchini purees due to their higher content of soluble pectin, while broccoli puree and, especially, tomato puree should be used in combination with other vegetables. Partial loss of functional and technological properties of vegetable raw materials due to excessive hydrolysis of pectin substances has a negative effect on the rheological characteristics os ice cream mixes. Fermented vegetable raw materials due to the higher content of soluble pectin and the formation of structuring complexes between polysaccharides and milk proteins, significantly affect the rheological characteristics of milk mixes. The effective viscosity of the practically intact structure of milk-vegetable mixes with vegetable purees hydrolyzed by an acid method is somewhat lower than mixes with fermented purees, which is explained by the thinning effect of pectinase on fragments of plant cell membranes. The effective viscosity of the recovered structure of milk-vegetable mixes with fermented vegetable purees shows a high thixotropic ability because of not only high content of soluble pectin, but also softened plant fibers. Such mixes can be attributed to systems with a pronounced coagulation structure and characteristic thixotropic properties. β-glucan as a soluble dietary fiber was chosen for alternative replacement of stabilizing systems in ice cream with a low content of fat and solids. It was showed that, compared to milk-protein concentrates, oat β-glucan exhibits higher technological activity in the composition of ice cream mixes, including its combination with soluble pectin of vegetable puree. It has been proven that the effective viscosity of ice cream mixes with oat β-glucan in the amount of 0.5…1.0% is in the range of recommended values. Mixes of milk ice cream with oat β-glucan are characterized by high thixotropic ability, which fully ensures the implementation of the technological cycle of ice cream production at the stage of dosing and forming its portions. The complex use of β-glucan and fermented vegetable purees with a high content of soluble pectin and the presence of softened vegetable fibers allows improving the viscosity-speed characteristics of mixes: the effective viscosity increases by 11.5…15.9%, and the degree of recovery by an average of 10%. Low-fat milk-vegetable ice cream with β-glucan as a natural structure stabilizer acquires a characteristic creamy consistency. The increase in overrun and resistance to melting of ice cream with β-glucan was observed due to formation of a specific secondary foam microstructure, which is characterized by the presence of an additional framework of microbubbles, that wraps larger air inclusions and gives them additional mechanical stability during heating. Fermented purees with a content of at least 1.0% soluble pectin have the greatest impact on the structural and mechanical characteristics of low-fat milk ice cream mixes in all its combinations with other structuring ingredients. Mixes of milk ice cream with oat β-glucan and vegetable purees at lower frequencies of measuring viscoelastic properties show elasticity, but after exceeding a certain frequency value, the structure is destroyed and the mixes show greater viscosity than elasticity, which will provide more intense air saturation of the mixes during freezing. A correlation between viscosity, water activity and surface tension of low-fat ice cream mixes was revealed, which is explained by intermolecular interaction between macromolecules of hydrocolloids and active binding of free water by a complex of low- and high-molecular compounds. A correlation between viscosity, water activity and surface tension of low-fat ice cream mixes was revealed, which is explained by intermolecular interaction between macromolecules of hydrocolloids and active binding of free water by a complex of low- and high-molecular compounds. An alternative substitute for the Cremodan SI 320 stabilization system in the amount of 0.5% in low-aft dairy ice cream is a complex of natural ingredients such as oat β-glucan and fermented purees in amounts of 0.5 and 15…25%, respectively. The functional and technological properties of pectin-containing purees from vegetables in the composition of ice cream with their varied content in the range from 10 to 35% were studied. The sensory indicators, content of soluble pectin, water activity and active acidity of milk-vegetable mixes, overrun and resistance to melting of milk-vegetable ice cream were selected as quality criteria of the studied samples. It was showed that the hydrolysis of protopectin reduces the water activity in vegetables and milk-vegetable mixes, according to the total content of soluble pectin. It has been proven that in a given content range, the solids of vegetables increase the resistance to melting of ice cream. According to the set of quality indicators of samples of milk ice cream with vegetables, it was determined that vegetable purees from carrots, beets and zucchini have the highest technological activity, while broccoli and tomato puree have the lowest technological activity. Based on the comparative analysis of the research results, recommendations were developed for the preparation of basic (typical) formulations of milk ice cream with vegetables, sherbet and vegetable ice cream, taking into account the rational ranges of content of fermented vegetable purees, including the combination of different types of vegetables. The technological modes of maturation of ice cream mixes with vegetable raw materials of different chemical composition have been specified. The normative indicators of the quality of milk ice cream with vegetables, vegetable ice cream and sherbet, including during storage, were studied. The social effect of the introduction of improved technology of ice cream with the use of vegetable raw materials consists in the expansion of the assortment line of ice cream of increased nutritional value based on exclusively natural raw materials, saving raw materials of animal origin, shortening the duration of the technological cycle of the production. The reliability of the obtained results was confirmed by the use of modern research methods, appropriate equipment, and the use of mathematical tools for processing the results. Scientific provisions and recommendations are confirmed by laboratory studies conducted in the laboratories of universities in Ukraine and Poland. The scientific novelty of the development was confirmed by the positive decision of the State Intellectual Property Department of Ukraine on the issuance of patents.
Keywords: овочі; ферментативний гідроліз; β-глюкан; молочні білки; ефективна в'язкість; активність води; органолептичні показники; ice cream; ice cream; pectin; vegetables; enzymatic hydrolysis; β-glucan; milk proteins; viscosity; water activity; organoleptic indicators; organoleptic indicators